Engineered platelets-based drug delivery platform for targeted thrombolysis - Songli Wang; Ruifeng Wang; Nana Meng; Linwei Lu; Jun Wang; Jianfen Zhou; Jiasheng Lu; Qianzhu Xu; Cao Xie; Changyou Zhan; Yao Li; Yang Yu; et al. (Elsevier, 2022)
Thrombolytic agents have thus far yielded limited therapeutic benefits in the treatment of thrombotic disease due to their short half-life, low targeting ability, and association with serious adverse reactions, such as bleeding complications. Inspired by the natural roles of platelets during thrombus formation, we fabricated a platelet-based delivery system (NO@uPA/PLTs) comprising urokinase (uPA) and arginine (Arg) for targeted thrombolysis and inhibition of re-embolism. The anchoring of uPA to the platelet surface by lipid insertion increased the thrombotic targeting and in vivo circulation duration of uPA without disturbing platelet functions. Nitric oxide (NO) generated by the loaded Arg inhibited platelet aggregation and activation at the damaged blood vessel, thereby inhibiting re-embolism. NO@uPA/PLTs effectively accumulated at the thrombi in pulmonary embolism and carotid artery thrombosis model mice and exerted superior thrombolytic efficacy. In addition, the platelet delivery system showed excellent thrombus recurrence prevention ability in a mouse model of secondary carotid artery injury. The coagulation indicators in vivo showed that the platelet-based uPA and NO co-delivery system possessed a low hemorrhagic risk, providing a promising tool for rapid thrombolysis and efficient inhibition of posttreatment re-embolism.